Allogeneic stem cell transplantation for children with acquired severe aplastic anaemia: a retrospective study by the Viva‐Asia Blood and Marrow Transplantation Group. (5th June 2013) - Chen, Jing; Lee, Vincent; Luo, Cheng Juan; Chiang, Alan Kwok Shing; Hongeng, Suradej; Tan, Poh Lin; Tan, Ah Moy; Sanpakit, Kleebsabai; Li, Chun Fu; Lee, Anselm Chi‐wai; Chua, Hsin Chieh; Okamoto, Yasuhiro
Summary: We retrospectively analysed the outcomes of 127 children with acquired severe aplastic anaemia (SAA) who had received haematopoietic stem cell transplantation (HSCT) between 2000 and 2011 in one of the 10 Asia Pacific institutions. Fifty‐three were matched sibling donor (MSD) and 74 were alternative donor (AD), including 22 matched unrelated donor, 32 mismatched unrelated donor and 20 mismatched related donor. With a median follow up 45·5 months (13–139) and when compared to the MSD group, AD recipients had more grade II‐IV acute graft‐versus‐host disease (aGVHD; 14·3% vs. 32·8%, P = 0·029), but similar grade III‐IV aGVHD (10·2% vs. 12·5%, P = 0·774), graft failure (GF) (15·1% vs. 15·5%, P = 0·658) and 5‐year overall survival (90·6% vs. 83·7%, P = 0·251). As a source of stem cell, peripheral blood stem cells (PBSC) resulted in less GF (18% vs. 9·1% P = 0·013), similar grade II‐IV aGVHD (28·1% vs. 17·4%, P = 0·258), chronic GVHD (25·8% vs. 29·3%, P = 0·822) and similar outcomes (89·7% vs. 82·4%, P =0 ·665) when compared to bone marrow (BM). In univariate analysis, GF ( P < 0·001) and grade II‐IV aGVHD ( P = 0·009) were predictors of poor survival. In multivariate analysis, only GF was associated with poor survival ( P = 0·012). The outcome of AD and PBSC HSCT were comparable to that of MSD and BM HSCT in the Asia Pacific region.